Human resource development in twentieth-century Japan nijisseiki Nihon no jinteki shigen / chosha Inoki Takenori ; yakusha Ton?i Gonzaresu. - Inoki, Takenori; Gonzalez, Tony (Tokyo Japan Publishing Industry Foundation for Culture, 2017)
"In this book, we will examine the formation and allocation of human resources that brought about economic growth, focusing on the form of education and training in schools, companies, and the military. In particular, how are knowledge and skills delivered in a 'have-not' country like Japan? Following transitions form the Edo period to the present age, we approach the core of Japanese systems from both historical and theoretical perspectives"--Back cover.
Education in the Edo and Meiji periods -- Industrialization and the labor force -- The military and industry -- Postwar schools and educational investment -- Human resource development in factories -- White-collar workers -- The public sector -- Emigration and immigration.
"This book is a complete translation of Z?oho gakk?o to k?oj?o : Nij?u-seiki nihon no jinteki shigen (Chikumashobo Ltd., 2016), which is a retitled and revised edition of a book first published in 1996 under the title Gakk?o to k?oj?o : Nihon no jinteki shigen, volume seven of the series Nij?u-seiki no nihon published by Yomiuri Shimbun"--Title page verso.
Includes bibliographical references (pages 244-259).
Text translated into English from Japanese.
Keywords: Education -- Social aspects -- Japan -- History; Education -- Japan -- History -- 1868-; Industrialization -- Japan -- History; Human capital -- Japan; Labor market -- Japan; Employees -- Training of -- Japan; Education -- Aspect social; Industrialisation -- Capital humain -- Ressources humaines -- Main-d'oeuvre -- Planification -- Personnel -- Formation -- Japon; Japon -- Histoire -- Histoire et critique -- 1600-1868(?Epoque d'Edo) -- Japon -- 1868-1912 (?Ere Meiji).